NUMERICAL METHOD FOR THE KINEMATIC ANALYSIS OF THE MCPHERSON GUIDING MECHANISMS USED FOR THE REAR WHEELS OF THE PASSENGER CARS - Alexandru, Cătălin (My University, 2018)
The paper deals with a numerical method for the kinematic analysis of the McPherson guiding mechanisms of the vehicle rear wheels with independent suspension. The kinematics of the mechanism is modeled by a non-linear system of 8 equations, regardless of the complexity of the mechanism in terms of number of elements, which is then solved by using the Newton-Kantorovich approach. A computer program was developed and tested on various McPherson suspension configurations.